Interactions between calcium intake and polymorphisms in genes essential for calcium reabsorption and risk of colorectal neoplasia in a two‐phase study. Issue 10 (15th June 2017) - Zhao, Jing; Zhu, Xiangzhu; Shrubsole, Martha J.; Ness, Reid M.; Hibler, Elizabeth A.; Cai, Qiuyin; Long, Jirong; Chen, Zhi; Jiang, Ming; Kabagambe, Edmond K.; Zhang, Bing; Hou, Lifang; et al.
Abstract : The SLC8A1 (solute carrier family 8, member 1) gene, encoding Na + /Ca 2+ exchanger, is essential in regulating calcium reabsorption and homeostasis. Calcium homeostasis plays a key role in cell proliferation and apoptosis. We hypothesized that polymorphisms in five calcium‐regulating genes ( SLC8A1, ATP2B1, CALB1, CALB2, and CABP1 ) interact with calcium intake in relation to the risk of colorectal neoplasia. A two‐phase (discovery and replication) study was conducted within the Tennessee Colorectal Polyp Study, including a total of 1275 cases and 2811 controls. In Phase I, we identified six out of 135 SNPs that significantly interacted with calcium intake in relation to adenoma risk. In Phase II, the calcium intake by rs4952490 ( SLC8A1 ) interaction was replicated (Pinteraction = 0.048). We found an inverse association between calcium intake (1000‐2000 mg/day) and colorectal adenomas, particularly for multiple/advanced adenomas, among the G‐allele carriers but not among homozygous carriers of the common variant (A) in rs4952490. In the joint analysis of SLC8A1, KCNJ1, and SLC12A1 SNPs, carriers of variant alleles in at least two genes and with calcium intake above the DRI (1000 mg/day) were approximately 30‐57% less likely to have adenomas than those whose calcium intake was below the DRI. The association was stronger for multiple/advanced adenomas. No association was found among those who did not carry any variant alleles in these genes when calcium intake was below 2500 mg/day. These findings, if confirmed, may provide a new avenue for the personalized prevention of colorectal adenoma and cancer.